Ego-Documents in the Structure of Historical Memory - S. V. Kozlov (Библиосфера)
The phenomenon of historical memory, while prominent in the present socio-humanitarian field has only recently drawn attention of book studies scholars in our country. It therefore becomes necessary in book culture scholarship to utilize the research potential of memory studies. This article focuses on ego-documents that include autobiographies, memoirs, diaries, and other documents of personal origin, to reveal their role in the structure of historical memory and to show how their publication affects their preservation. The article shows that ego-documents as specific social practices function as institute for creation, preservation, and transmission of historical memory. Approaches and methods of memory studies utilized in this article can be used to develop methodological approaches for the research project pursued by the State Public Scientific and Technological Library of the Siberian Branch of the Russian Academy of Sciences entitled “Ego-documents on the history of the Great Patriotic War and other 20th century military conflicts in the archival depositories of Eastern Russia: problems of location, attribution, and publication”